Digital Learning Transformation through AWBIT: A Case Study on the Department of Mathematics Education, State University of Medan - Elfitra Elfitra; Edi Syahputra; Badzlan Darari; Suci Frisnoiry; Nerli Khairani (Jurnal Ilmu Pendidikan, 2025)
This study aims to examine the effectiveness of Adaptive Web-Based Interactive Tutoring (AWBIT) in transforming digital learning and improving students' digital literacy in the Calculus course at the Department of Mathematics Education, State University of Medan. The study used a quasi-experimental method with a Nonequivalent Control Group Design, involving two classes as experimental and control groups. The experimental group used AWBIT, while the control group used conventional learning. The instruments used include pretest and posttest tests, student response questionnaires, and validation of material and media experts. The validation results showed that AWBIT was very feasible to use with an average score of 3.38 from material experts and 3.43 from media experts. Students responded positively to AWBIT with an average questionnaire score of 3.35 and an practicality of use at 3.75 high.Statistical tests show that the data is distributed normally and homogeneously. The results of the t-test showed a significant difference between the learning outcomes of the experimental and control groups, with a gain score of 0.61 in the experimental group and 0.34 in the control group. These findings show that AWBIT is effective in improving students' learning outcomes and digital literacy. This system provides adaptive, interactive, and personalized learning, according to the individual needs of students. This research supports the integration of technology in learning and is in line with the implementation of the Independent Curriculum and the Outcome-Based Education (OBE) approach in higher education.